2016
DOI: 10.1093/humrep/dex074
|View full text |Cite
|
Sign up to set email alerts
|

Single versus repeat doses of misoprostol for treatment of early pregnancy loss—a randomized clinical trial

Abstract: 19 August 2015.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 17 publications
4
11
0
Order By: Relevance
“…The overall success rate of medical treatment in our study was 75%, which is similar to rates reported in the literature (3,4,9,10).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The overall success rate of medical treatment in our study was 75%, which is similar to rates reported in the literature (3,4,9,10).…”
Section: Discussionsupporting
confidence: 90%
“…As opposed to surgical management, namely dilation & curettage (D&C), the advantages of medical treatment in cases of EPL are well known. Nevertheless, up to 30% of patients treated medically will ultimately require an additional surgical procedure (3,4,6). When counselling patients with EPL regarding the optimal treatment, we prefer to tailor therapy based on the individual patient's characteristics and predictors of success.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The same is reported to be 16% in another study. 16 Overall the results of this study are almost parallel to the research work reported in other similar studies.…”
Section: Discussionsupporting
confidence: 90%
“…The same dosage schedule is used in another study and they showed an overall success rate of 77%. 16 The largest randomized controlled trial conducted in the United States of America (USA) demonstrated 71% expulsion with first dose of Misoprostol by day 3 and increased to 84% with the 2 nd dose (800 microgram). For surgical evacuation, a success rate of 93% was reported.…”
Section: Discussionmentioning
confidence: 99%